Cooperative Principles and Cooperative Practice – Communal Housing in the City of Leipzig - Wiest, Karin; Baldin, Marie-Luise; Hildebrandt, Sophia; Montanari, Giulia (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
Shortage of housing, rising real estate prices and discussions about the ‘Right to the City’ build the background to a revival of cooperative housing models in German cities. Associative forms of housing, traditionally represented by housing cooperatives, seem to be especially suited to respond to the newly arising housing needs of an individualised and aging society. Still, the collective organization of housing appears in diverse forms and partly appeals to quite different target groups. At the same time, opportunities to act for cooperative players are greatly influenced by regional and local conditions. In former Eastern Germany long prevailing phenomena such as vacancy and deconstruction are lately being replaced by new social challenges such as the increasing tendencies to segregation and the change of generation of the housing association members. Against this backdrop, the following article is dealing with the relation between cooperative principles and the everyday needs, interest and practice of the members of a traditional housing cooperative in the city of Leipzig. The collective housing projects that were established on the local housing market in recent years serve as a frame of reference for the findings on the self-conceptions of the surveyed housing cooperatives.